(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
The article examines the reception and different readings that La Araucana had in Chile, in the last decades of the 19th century and first decades of the 20th century. At the same time, the modality in which these readings are part of a nationalism that differs from the liberal nationalism of the 19th Century. It outlines the characteristics of the new imaginary of the nation and the impact it had in the reception of Ercilla’s work. The article follows the chilenization of La Araucana in literary historiography and in the publishing field, also in musical nationalism and in the debates of the so called scientific Araucanismo and in the idea of a supposed Chilean Race. Finally, it establishes a link with other articles by the same author that contribute to the study of the reception and resemantization of La Araucana.